An Update of Management of Idiopathic Nephrotic Syndrome: A Review Article (Bangladesh Journal of Child Health, 2013)
Nephrotic syndrome (NS) is a common childhood kidney disease characterized by protein leakage from the blood to the urine through the glomeruli, resulting of proteinuria, hypoalbuminemia, generalized edema and hypercholesterolemia. The prevalence of minimal change nephrotic syndrome is higher in Indian subcontinent. Such incidence in Bangladesh is yet unknown. This review article discusses historical background, epidemiology, pathogenesis, pathophysiology and classification of nephrotic syndrome. In this review article focuses have been made on management of children aged between 1 to 18 years with idiopathic nephrotic syndrome. This article also provides information of different guideline recommendations and a brief review of relevant treatment trials related to each recommendation. DOI: http://dx.doi.org/10.3329/bjch.v37i2.17268 BANGLADESH J CHILD HEALTH 2013; VOL 37 (2) : 102-121